Pemetaan Konseptual Kajian Feminisme melalui Analisis Bibliometrik Visual terhadap Literatur Tahun 2015–2025 - Wardani, Hesti Ari; Yuadi, Imam (Universitas Nasional, 2025)
This study aims to map the conceptual structure of feminist scholarship through a visual bibliometric approach using data from Google Scholar, collected via the Publish or Perish software and analyzed with VOSviewer. A total of 1,000 academic articles published between 2013 and 2023 were analyzed. Three types of visualizations—density, overlay, and network—were employed to identify thematic density, temporal trends, and keyword co-occurrence within the literature on feminism. The results show that terms such as second wave feminism, radical feminism, and popular feminism dominate the field and serve as the foundation of contemporary feminist discourse. Meanwhile, terms such as white feminism, transnational feminism, and methodology have recently emerged, indicating a shift in research interest toward more reflective, intersectional, and global feminist frameworks. The network visualization reveals distinct thematic clusters that illustrate the complexity and diversity of feminist approaches. These findings suggest that feminist scholarship is evolving from ideological roots toward more methodological and transnational reflexivity. This study contributes to the intellectual mapping of feminism and provides a basis for future interdisciplinary and context-specific feminist research.